POST-MORTEM CHANGES IN METABOLOMIC PROFILES OF HUMAN SERUM, AQUEOUS HUMOR, AND VITREOUS HUMOR - RIAZ, L; SIDDIQUI, AM; RASHID, MN; SHAHID, RA; NASRULHUDA, .; BUTT, F (Biological and Clinical Sciences Research Journal, 2024)
Accurate post-mortem interval (PMI) estimation is crucial in forensic investigations, and metabolomic analysis of bodily fluids offers a promising approach. However, the suitability of ocular fluids for PMI estimation remains underexplored. Objective: The objective of this study was to evaluate the suitability of metabolomic analysis of ocular fluids, specifically vitreous humor (VH) and aqueous humor (AH), compared to serum for post-mortem interval (PMI) estimation and to identify the most promising metabolites for this purpose. Methods: A cross-sectional study was conducted at a tertiary care hospital in Karachi. Blood, AH, and VH samples were collected from human cadavers with PMIs ranging from 5 to 60 hours. Samples were prepared by removing proteins and lipids, followed by lyophilization. Metabolomic profiling was performed using an NMR Spectrometer. Pearson correlation coefficients were calculated to assess the relationship between metabolite concentrations and PMI. Results: The study identified 24 metabolites in blood, AH, and VH samples. Several metabolites, including glutamate, choline, glycine, and formate, exhibited significant positive correlations with PMI in all three fluids, with Pearson coefficients greater than 0.5. Notably, glutamate (blood: r = 0.585**, AH: r = 0.488*, VH: r = 0.683**), choline (blood: r = 0.435*, AH: r = 0.691**, VH: r = 0.713**), and glycine (blood: r = 0.553*, AH: r = 0.598**, VH: r = 0.690**) showed strong correlations. Conversely, glucose and pyruvate significantly negatively correlated with PMI in AH and VH. Conclusion: The findings indicate that VH and AH are more reliable than serum for PMI estimation due to their more stable metabolite profiles. Glutamate, choline, and glycine emerged as particularly promising biomarkers. The study supports the potential of metabolomic analysis of ocular fluids in forensic investigations to provide accurate PMI estimations.